Avaliação dos serviços educacionais do Núcleo de Prática Jurídica: relevância para a formação discente de nível universitário. - Pereira Neto, Milton (2024)
The research focused on evaluating the perspectives of students, faculty, and administrative members regarding the quality of services offered by the Legal Practice Center (NPJ) at Estacio Amapa University. The primary objective was to identify both the positive aspects and those that required improvement in the NPJ, aiming to propose measures that would elevate the level of activities conducted in that environment. The purpose of this work was, therefore, to contribute to the advancement of scientific knowledge and the refinement of practices in the field of legal education, with a particular focus on the Amapa reality. The adopted methodological strategy embraced an applied approach, involving a thorough exploration of the regulations and norms that guided legal education and the functioning of the NPJ. Additionally, the study addressed a historical perspective on legal education in Brazil, emphasizing the importance of Legal Practice Centers for the training of future lawyers and the social impact of activities conducted in that legal practice laboratory. One of the most essential aspects was to unveil the perspectives and actions of the various stakeholders, including students, faculty, and administrative professionals. In this sense, the research investigated and described the teaching, extension, and research activities practiced within the NPJ at Estacio Amapa University, especially the exogenous activities such as community service, equivalent internships, free legal assistance, community legal education, among others, as well as the endogenous activities like mandatory internships, case studies, simulated practices, lectures, and others. Similarly, it examined how students perceived the activities carried out and how such perspectives influenced their opinions and suggestions. The predominant methodological approach was qualitative, allowing for a holistic understanding of the interconnection between legal education and the NPJ. The temporal scope of that research extended from the period of 2021.2 to 2023.1, thus encompassing a longitudinal perspective. Data collection was conducted through interviews with coordinators, faculty advisors, administrative professionals, and other key agents of the NPJ. The sampling approach was intentional and non-probabilistic, aiming to select participants with relevant experience and expertise. For students, an open and voluntary questionnaire was offered, providing a thorough examination of their experiences. The core of data analysis relied on the content analysis methodology, playing a central role in interpreting the collected data to identify significant trends and patterns. The obtained results were contextualized with existing literature and relevant regulations, thereby providing valuable insights to optimize the functioning of the NPJ. It is worth noting that the research was conducted at Estacio Amapa University, located in Macapa, Amapa, and duly accredited by the Ministry of Education. Through this approach, the aim was to significantly enhance legal education practices and gain a deeper understanding of the role played by the NPJ in the training of future legal professionals.